2007
DOI: 10.1152/jn.00354.2007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Reaching Kinematics and Prehensile Dexterity in Nonhuman Primates

Abstract: A modified "Klüver" or dexterity board was developed to assess fine control of hand and digit movements by nonhuman primates during the acquisition of small food pellets from wells of different diameter. The primary advantages of the new device over those used previously include standardized positioning of target food pellets and controlled testing of each hand without the need for restraints, thereby allowing the monkey to move freely about the cage. Three-dimensional video analysis of hand motion was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(101 citation statements)
references
References 40 publications
1
100
0
Order By: Relevance
“…The present behavioral tests, used since several years in our laboratory to quantify manual dexterity, are to some extent comparable to other tests of manual dexterity recently reported in the literature [24][25][26][27][28] . There is however a crucial need to standardize tests across different laboratories (for better comparison), which is a tentative goal of the present report.…”
Section: Figuresupporting
confidence: 76%
“…The present behavioral tests, used since several years in our laboratory to quantify manual dexterity, are to some extent comparable to other tests of manual dexterity recently reported in the literature [24][25][26][27][28] . There is however a crucial need to standardize tests across different laboratories (for better comparison), which is a tentative goal of the present report.…”
Section: Figuresupporting
confidence: 76%
“…In this model, the primary motor cortex and lateral premotor cortex controlling the preferred arm of the animal were specifically lesioned by aspiration=coagulation, as performed in human neurosurgery for the selective removal of tumors, epileptogenic foci, and arteriovenous malformations. Following resection, the animals recovered most of their limb functions during the recovery period (Darling et al, 2006;Pizzimenti et al, 2007). Our results demonstrated that microglia activation, as indicated by positive immunoreactivity to a phagocytic marker, CD68, was observed not only at the site of injury but also in the cervical spinal cord for up to 12 months after the injury .…”
mentioning
confidence: 59%
“…The preparation and procedure of animal surgery were performed as previously described (Darling et al, 2006;Morecraft et al, 2001Morecraft et al, , 2002Morecraft et al, , 2004Morecraft et al, , 2007Nagamoto-Combs et al, 2007;Pizzimenti et al, 2007). Briefly, each animal was prepared for surgery by an initial administration of ketamine hydrochloride (10 mg=kg) and kept anesthetized during cortical exposure with a continuous administration of isofluorane (1-1.5% with surgical grade air=oxygen mixture) with the assistance of a mechanical respirator.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations